2002
DOI: 10.1021/ja025779m
|View full text |Cite
|
Sign up to set email alerts
|

Estimating pKa Values for Pentaoxyphosphoranes

Abstract: pKa values are estimated independently, by two entirely different methods, for the ionizations of the apical and equatorial OH groups of two representative hydroxyphosphoranes. A bond length-pKa correlation based on crystal structures of cyclohexanol derivatives gives values of 13.5 +/- 1.5 and 8.62 +/- 1.87, respectively, for the apical and equatorial OH groups of tetracyclohexyloxyhydroxyphosphorane, and an ab initio molecular dynamics calculation gives values of 14.2 and 9.8 for the corresponding first ioni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
150
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(161 citation statements)
references
References 25 publications
10
150
1
Order By: Relevance
“…This approach has been successfully applied in some cases, e.g. water (Sprik, 2000) and pentaoxyphosphoranes (Davies et al, 2002;Doltsinis and Sprik, 2003).…”
Section: Methods Of Constraintmentioning
confidence: 99%
“…This approach has been successfully applied in some cases, e.g. water (Sprik, 2000) and pentaoxyphosphoranes (Davies et al, 2002;Doltsinis and Sprik, 2003).…”
Section: Methods Of Constraintmentioning
confidence: 99%
“…Other studies have shown this type of proton transfer can be controlled by constraining the proton coordination number of O w . 45, 51 The contribution of entropy to ∆F is small, at least in P-O s bond breaking (see reaction maxima in Figure 8a). The experimental results of George et al 9 indicate that the entropy contribution in pyrophosphate hydrolysis is -1.4 kcal/mol at 298 K. The solvent structure in our final configuration is not fully relaxed, since the displacement of the metaphosphate has created a small cavity.…”
Section: A Properties Of Triphosphate Molecules and Solvatedmentioning
confidence: 99%
“…Since that encouraging study, the methodology has been applied on more complicated condensed phase systems, e.g. pentaoxyphosphoranes (Davies et al, 2002;Doltsinis and Sprik, 2003), Al-aqua and Si(OH) 4 (Liu et al, 2010a), and carbonic acid conformers (Liu et al, 2010b). Recently, Churakov and Kosakowski (2010) employed FPMD to study the transfer events of excess protons occurring in the interlayer regions of smectites and found that similar to the bulk, the proton transfer processes are barrier free.…”
Section: Introductionmentioning
confidence: 99%